2021
DOI: 10.1101/2021.01.22.427843
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Circuit organization of the excitatory sensorimotor loop through hand/forelimb S1 and M1

Abstract: Sensory-guided limb control relies on communication across sensorimotor loops. For active touch with the hand, the longest loop is the transcortical continuation of ascending pathways, particularly the lemnisco-cortical and corticocortical pathways carrying tactile signals via the cuneate nucleus, ventral posterior lateral (VPL) thalamus, and primary somatosensory (S1) and motor (M1) cortices to reach corticospinal neurons and influence descending activity. We characterized excitatory connectivity along this p… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 89 publications
0
1
0
Order By: Relevance
“…Earlier work has shown that in addition to targeting L1, long-range input from cortical areas like M1 targets infragranular layers (Geng et al, 2021;Kinnischtzke et al, 2016;Yamawaki et al, 2021;Zagha et al, 2013). This raises the question whether neurons that project to L1 from other brain areas are presynaptic to the L5 pyramidal neurons?…”
Section: Long-range Input To L1 and L5 Neuronsmentioning
confidence: 99%
“…Earlier work has shown that in addition to targeting L1, long-range input from cortical areas like M1 targets infragranular layers (Geng et al, 2021;Kinnischtzke et al, 2016;Yamawaki et al, 2021;Zagha et al, 2013). This raises the question whether neurons that project to L1 from other brain areas are presynaptic to the L5 pyramidal neurons?…”
Section: Long-range Input To L1 and L5 Neuronsmentioning
confidence: 99%